Transcription factors: tools to engineer the production of pharmacologically active plant metabolites - Gantet, P.; Memelink, J.
Plants produce a variety of secondary metabolites, some of which are used as pharmaceuticals or are health promoting as food components. Recent genetic studies on the flavonoid biosynthetic pathway show that transcription factors are efficient new molecular tools for plant metabolic engineering to increase the production of valuable compounds. The use of specific transcription factors would avoid the time-consuming step of acquiring knowledge about all enzymatic steps of a poorly characterized biosynthetic pathway. Although genetic approaches are difficult for most plant species, promoter studies of single-pathway genes and T-DNA activation tagging are feasible alternative approaches for isolating transcription factors, as illustrated for terpenoid indole alkaloid biosynthesis in Catharanthus roseus. Recent genetic studies on the flavonoid and alkaloid biosynthetic pathways show that transcription factors are efficient new molecular tools for plant metabolic engineering to increase the production of valuable pharmaceuticals.
Keywords: TRANSCRIPTION FACTORS; CATHARANTHUS ROSEUS; ALKALOID; METABOLIC ENGINEERING; FLAVONOID; PHARMACEUTICAL COMPOUNDS; NUTRACEUTICAL; PLANT PHARMACEUTICAL; L COMPOUNDS; FUNCTIONAL FOOD